The Components of Social Dimension for Community Gardens in Housing Residential - Abdullah Ayeop, Shafa Marzidah; Zainol, Halmi; Mohd Hussain, Nur Huzeima (Environment-Behaviour Proceedings Journal, 2018)
Community gardens are known as space for people to plant vegetables and fruits for their daily use. Various social benefits could be obtained through the implementation of community gardens in the urban neighbourhoods. This paper aims to give a better understanding relationship between the social dimension and community garden. The objectives of this paper are to identify the social dimension elements of sustainable development and to explore the benefits from community garden implementation towards social dimension. This paper analyses established references from previous articles and theses to identify a relationship between the social dimension and community garden.